Evaluasi Program One Muhammadiyah One Response (OMOR) Dalam Penanggulangan Bencana Alam: Sebuah Studi Observasi di Kabupaten Magelang Indonesia - Margono, ABS; Amin, Muhammad Khoirul; Handayani, Estrin (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Indonesia is a region where natural disasters, such as earthquakes, tsunamis, volcanic eruptions, floods,landslides, and others have potentially happened. Natural disasters that occur in Indonesia generally havecaused facilities, material losses, and psychological impacts. Muhammadiyah Central Management DisasterManagement Agency has an English term "Muhammadiyah Disaster Management Center" or abbreviated asMDMC. MDMC is engaged in disaster management activities by the definition of disaster managementactivities both in mitigation and readiness also in emergency response and rehabilitation activities. MDMCadopts an international code of humanitarian volunteerism and humanitarian charter to develop disaster riskreduction missions in line with the Framework for Action and develops a base of preparedness at thecommunity, school, and hospital levels since 100 years ago. This research was conducted in the District ofMagelang and was carried out using a descriptive quantitative approach and action research by carrying outa literature study, survey, desk analysis, exploration; Instrument Development & Preliminary Research; DataCollection and Identification of Problems; FGD (Focus Group Discussion); Policy identification andformulation of the role of Muhammadiyah. This study was able to evaluate the implementation of the OMORprogram in Magelang regency which is not yet maximally satisfactory. From the contextt evaluation variable43% of the planning, documents were illustrated, 42.8% of the input variables were specifically carried out inthe program, and 34.2% of the process variables were implemented according to plan and 44.4% of the outputproduct variables completed program reports entirely. In this OMOR program in planning, implementing, and